Estratégias de marketing nas midias sociais no processo de consolidação de microempresas na comunidade do Macurany – cidade de Parintins/AM - Alves, Wanderley Pereira (Brasil, 2025)
Social media has become an indispensable channel for businesses of all sizes to reach their target audiences. With billions of active users across multiple platforms, social media offers enormous potential to increase brand visibility, generate leads, and drive sales. This study investigated the use of digital marketing strategies, specifically in social media, by three micro and small enterprises (MSEs) located in the Macurany region, in Parintins/AM. The main objective was to understand how these companies use these tools, the challenges faced and the results obtained in terms of sales. The research, of a qualitative and descriptive nature, involved the application of questionnaires and a systematic mapping of the companies. The results indicated that MSEs in the region recognize the importance of social media for the dissemination of their products and services, but face challenges such as lack of technical knowledge and difficulty in creating quality content. Despite the challenges, companies that invested more in digital marketing and adopted more effective strategies, such as producing relevant content and interacting with the public, achieved positive results in terms of increased sales.